Empathy from the client's perspective: A grounded theory analysis. (4th March 2017) - MacFarlane, Peter; Anderson, Timothy; McClintock, Andrew S.
Abstract: Although empathy is one of most robust predictors of client outcome, there is little consensus about how best to conceptualize this construct.Objective: The aim of the present research was to investigate clients' perceptions and in-session experiences of empathy.Method: Semi-structured, video-assisted interpersonal process recall interviews were used to collect data from nine clients receiving individual psychotherapy at a university psychology clinic.Results: Grounded theory analysis yielded a model consisting of three clusters: (1) relational context of empathy (i.e., personal relationship and professional relationship), (2) types of empathy (i.e., psychotherapists' cognitive empathy, psychotherapists' emotional empathy, and client attunement to psychotherapist), and (3) utility of empathy (i.e., process-related benefits and client-related benefits).Conclusions: These results suggest that empathy is a multi-dimensional, interactional process that affects—and is affected by—the broader relationship between client and psychotherapist.